2020
DOI: 10.1371/journal.pgen.1009020
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Tbc1d21 gene causes male infertility with morphological abnormalities of the sperm mitochondria and flagellum in mice

Abstract: Approximately 2-15% of couples experience infertility, and around half of these cases are attributed to male infertility. We previously identified TBC1D21 as a sterility-related RabGAP gene derived from infertile men. However, the in vivo function of TBC1D21 in male fertility remains unclear. Here, we show that loss of Tbc1d21 in mice resulted in male infertility, characterized by defects in sperm tail structure and diminished sperm motility. The mitochondria of the sperm-tail had an abnormal irregular arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…6 B ) and that KO spermatozoa from the cauda epididymis have an abnormality in the midpiece ( Fig. 6 C ), similar to a recently published study ( 33 ). To check mitochondrial sheath formation in Tbc1d21 KO male mice, we performed freeze-fracture SEM analysis.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…6 B ) and that KO spermatozoa from the cauda epididymis have an abnormality in the midpiece ( Fig. 6 C ), similar to a recently published study ( 33 ). To check mitochondrial sheath formation in Tbc1d21 KO male mice, we performed freeze-fracture SEM analysis.…”
Section: Resultssupporting
confidence: 89%
“…5 C ). Because TBC1 domain family protein TBC1D21 is the only TBC1 domain family protein showing testis-enriched expression in mice ( 20 ) and disruption of Tbc1d21 causes male infertility with morphological abnormalities of the sperm mitochondria ( 33 ), we focused on TBC1D21. We performed RT-PCR and confirmed that Tbc1d21 shows testis-enriched expression in mice and humans ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Armadillo repeat‐containing 12 (ARMC12) and TBC1 domain family member 21 (TBC1D21) are essential for mitochondrial elongation after alignment at mid‐piece in mice. 115 , 116 In Armc12 –KO mice, although spherical mitochondria are normally arranged on mid‐piece, their elongation and interlocking with adjacent mitochondria are impaired. As a result, a disorganized MS is formed, and sperm motility is decreased.…”
Section: Proteins Compose the Axonemal Structurementioning
confidence: 99%
“…Previous studies in animal models have suggested that TBC1D21 is crucial for mitochondrial and axoneme development in mammalian sperm through interaction with TOMM20 and DNAH7. 18 Therefore, we speculate that DNAH7 is vital for the formation of a functional complex with TBC1D21 and TOMM20, and that it might participate in the formation of intact mitochondrial structures in human sperm. From a clinical perspective, positive live birth after ICSI also represents a significant step towards the development of genetic diagnosis and counselling regarding prognosis.…”
Section: Discussionmentioning
confidence: 89%